Universal healthcare coverage, patients' rights, and nurse-patient communication: a critical review of the evidence - Abukari Kwame; Pammla M. Petrucka (BMC, 2022)
Abstract The Sustainable Development Goals adopted by world leaders on September 25, 2015, aimed to end poverty and hunger, promote gender equity, empower women and girls, and ensure human dignity and equality by all human beings in a healthy environment. These development goals were premised on international human rights norms and institutions, thereby acknowledging the relevance of human rights in achieving each goal. Particularly, sustainable development goal 3, whose objective is to achieve universal health coverage, enhance healthy lives, and promote well-being for all, implicitly recognizes the right to health as crucial. Our focus in this paper is to discuss how promoting patients' rights and enhancing effective nurse-patient communication in the healthcare setting is a significant and necessary way to achieve universal health coverage. Through a critical review of the empirical research evidence, we demonstrated that enhancing patients' rights and effect nurse-patient communication will promote people-centered care, improve patients' satisfaction of care outcomes, increase utilization of care services, and empower individuals and families to self-advocate for their health. These steps directly impact primary healthcare strategies and the social determinants of health as core components to achieving universal health coverage. We argue that without paying attention to the human rights dimensions or employing human rights strategies, implementing the other efforts will be inadequate and unsustainable in protecting the poorest and most vulnerable populations in the achievement of goal 3.